Decrease in preovulatory serum estradiol is a valuable marker for predicting premature ovulation in natural/unstimulated in vitro fertilization cycle - Xuefeng Lu; Shuzin Khor; Qianqian Zhu; Lihua Sun; Yun Wang; Qiuju Chen; Ling Wu; Yonglun Fu; Hui Tian; Qifeng Lyu; Renfei Cai; Yanping Kuang (BMC, 2018)
Abstract Background Premature ovulation occurs at a high rate in natural-cycle in vitro fertilization (IVF), and cycle cancellation further hampers the overall efficiency of the procedure. While lower levels of estradiol (E2) are observed in preovulatory follicles, it is unclear whether declines in E2 can be used as an effective marker of premature ovulation. Methods This retrospective analysis includes 801 natural/unstimulated IVF/ICSI cycles undergoing scheduled ovum pick-up (OPU) and 153 natural/unstimulated IVF/ICSI cycles undergoing emergency OPU at a university IVF center from May 2014 to February 2017. Results Among the 801 IVF/ICSI cycles undergoing scheduled OPU, preovulatory E2 levels increased by more than 10% in 403 (50.31%) cycles of the sample (Group A), while 192 (23.97%) cycles experienced a plateau (increased or decreased by 10%; Group B), and 206 (25.72%) cycles decreased by more than 10% (Group C). Group C had more patients who experienced premature LH surges, premature ovulation, as well as the fewest oocytes retrieved, frozen embryos, and top-quality embryos. A multivariate logistic regression analysis indicated that premature ovulation was associated with preovulatory E2/−1E2 ratio and premature LH surge. Moreover, preovulatory E2/−1E2 ratio served as a valuable marker for differentiating premature ovulation, with an AUC (area under the receiver operating curve) of 0.708 and 0.772 in cycles with premature LH surges and cycles without premature LH surges, respectively. Emergency OPU resulted in a significantly decreased rate of premature ovulation and increased number of frozen embryos. Conclusion Decreases in preovulatory serum E2 was a valuable marker for premature ovulation in natural/unstimulated IVF cycle. Emergency OPU based on the preovulatory E2/−1E2 ratio decreased the rate of premature ovulation in cycles that experienced E2 decreases.